Looking Back, Looking Around George Piper Dances - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2006)
George Piper Dances. Lorent intimates a tender world of compromised aspirations and submerged desires. PALABRAS CLAVE: George Piper Dances company, Michael Nunn, William Trevitt, Oxana Panchenko.